VIDEO KIMIA ONLINE BERBASIS PEMBELAJARAN KONTEKSTUAL SEBAGAI ALTERNATIF MEDIA PADA MATERI ASAM BASA DI SMA - Paristiowati, Maria; N, Muktiningsih; Rahma, Wanda Amelia (Lembaga Penelitian UM Metro, 2017)
This study aims to produce video of contextual learning as an alternative media on the acid-base in grade 11. The study was conducted using method of Research and Development (R&D) of Borg and Gall. Stages of the study are: (1) research and information collecting, (2) planning, (3) develop primary form of product, (4) preliminary field testing, (5) main product revision, (6) main field testing, (7) operational product revision, (8) operational field testing, (9) final product revision. The results of product testing at the final stage by subject matter experts and media experts give score from 75% -100%. This criterion are good and very good. While the results of trial by users (students and teachers) give score from 81.3% -88.9%, which means very good. The result of this study was concluded that video online can used as a media of learning contextual-based chemistry.